Distribution of sugarcane aphids and their predators on Kansas sorghum! - Heinitz, Brandon; Zukoff, Sarah (My University, 2017)
Sugarcane aphids (SCA) can have a severe impact on Kansas sorghum grain yields due to their high reproductive capacity and the copious amounts of honey dew they produce. There are many predatory species in Kansas that feed on SCA and help to reduce their impact on the sorghum plants. To understand how these predators affect the behavior of SCA on sorghum plants, we examined a sorghum field that was heavily infested with SCA and recorded the distributing and species of aphids and predators present. Overall, the aphids preferred to be in a semi-clumped distribution on the leaves when higher numbers of predators were present. Syrphid larvae were the most abundant predator and were almost always found within aphid clumps.